Healthcare needs among unaccompanied minor refugees: a study protocol of a qualitative study explaining access and utilisation across place and gender - Matthias Richter; Jacob Spallek; Hanna-Sophie Ulrich; Emma Kohler; Eva-Maria Fach; Martin Mlinarić (BMJ Open, 2020)
Introduction Several studies have identified that unaccompanied minor refugees (UMRs) are allegedly ‘vulnerable’ and belong to a high-risk group in terms of psychological distress and post-traumatic stress disorder due to their preflight, periflight and postflight experiences. Psychosocial care (PSC) is of high importance for UMRs, but little is known about barriers to access and utilisation of PSC across place and gender. The aims of this gender-sensitive qualitative study will be to build on the existing body of literature and to provide qualitative evidence on the contexts and mechanisms of PSC for male and female UMRs in Germany by comparing two German regions.Methods and analysis Following the study preparing realist review, a qualitative study will be undertaken in Berlin and Central German cities. Approximately 24 experts from the field of PSC and 12 lay UMRs will participate in face-to-face, semistructured interviews. Data will be transcribed and analysed based on the grounded theory research paradigm.Ethics and dissemination Only participants who have been informed in both German and their native tongue and who have signed a declaration of consent will be included in the study. The study will comply rigorously with German data protection standards. Approval from the Ethical Review Committee at Martin Luther University Halle-Wittenberg, Germany has been obtained and granted. The results of the study will be presented at several conferences and will be published in high-quality, peer-reviewed international journals. The results will display a differentiated picture of the PSC of UMRs in Germany. Such knowledge is a precondition for a ‘science of change’ that translates explanations into practical recommendations on how to improve healthcare policies.Trial registration number DRKS00018080.